A 365 nm UV LED-excitable antenna ligand for switchable lanthanide luminescence. Issue 13 (31st May 2017) - Lahdenperä, Susanne; Wang, Qi; Vainio, Jiri; Soukka, Tero
Abstract : Synthesis and evaluation of a new 365 nm excitable antenna ligand for Eu III employed in switchable lanthanide luminescence. Abstract : The time-resolved luminescence of lanthanide complexes is a highly sensitive and widely used bioassay technology for clinical diagnostics. With the time-resolved luminescence detection the naturally occurring autofluorescence of biological matrices, solid supports and plastics can be avoided. A major drawback of the current technique is that the luminescent lanthanide labels require ultraviolet (UV) excitation, typically shorter than 360 nm, which is strongly absorbed and can damage living biological systems. The lack of cost-efficient high power solid state excitation light sources for UV excitation further limits the development of low-cost and more compact measurement instruments for time-resolved luminescence and the potential use of lanthanide luminescence in different applications. Switchable lanthanide luminescence is a binary probe technology that inherently enables a high signal modulation in a separation-free detection of targets. The intrinsically luminescent lanthanide chelate is split into two nonluminescent moieties, a lanthanide ion carrier chelate and a light harvesting antenna ligand, each of which can be attached to a separate molecular probe. A luminescent lanthanide complex is formed only when the two probes bind adjacently to the target molecule. Herein we describe a new 365 nm excitable antenna ligand (AL360) for switchable lanthanide luminescence of europium(iii ) (Eu III ) that would enable the use of 365 nm light emitting diodes (LEDs) as an excitation light source for time-resolved fluorescence imaging and detection. With the acquired subpicomolar assay sensitivity it would be applicable for solution or surface arrays and UV LED microscopy.